Nurses in Australian general practice: implications for chronic disease management - Halcomb, E.; Davidson, Patricia; Salamonson, Y.; Ollerton, R.; Griffiths, R. (Wiley-Blackwell, 2008)
Aims. The purpose of this study was to describe the demographic and employmentcharacteristics of Australian practice nurses and explore the relationship betweenthese characteristics and the nurses? role.Background. Nursing in general practice is an integral component of primary care andchronic disease management in the United Kingdom and New Zealand, but inAustralia it is an emerging specialty and there is limited data on the workforce and role.Design. National postal survey embedded in a sequential mixed method design.Methods. 284 practice nurses completed a postal survey during 2003?2004.Descriptive statistics and factor analysis were utilized to analyse the data.Results. Most participants were female (99%), Registered Nurses (86%), employedpart-time in a group practice, with a mean age of 458 years, and had a hospital nursingcertificate as their highest qualification (63%). The tasks currently undertaken byparticipants and those requiring further education were inversely related(R2 0779). Conversely, tasks perceived to be appropriate for a practice nurse and those currently undertaken by participants were positively related (R2 08996).There was a mismatch between the number of participants who perceived that aparticular task was appropriate and those who undertook the task. This disparity wasnot completely explained by demographic or employment characteristics. Extrinsicfactors such as legal and funding issues, lack of space and general practitioner attitudeswere identified as barriers to role expansion.Conclusion. Practice nurses are a clinically experienced workforce whose skills are notoptimally harnessed to improve the care of the growing number of people with chronicand complex conditions.Relevance to clinical practice. Study data reveal a need to overcome the funding,regulatory and interprofessional barriers that currently constrain the practice nurserole. Expansion of the practice nurse role is clearly a useful adjunct to specialistmanagement of chronic and complex disease, particularly within the context ofcontemporary policy initiatives.